A Comprehensive Systematic Review of The Relationship Between Serum Progesterone Levels and the Success of Maintaining Pregnancy in Threatened Miscarriage - Made Ega Krisna Prananda; Ketut Ananda Wiratama; Irwin Lamtota Lumbanraja; Igam Aditya Prasada (International Medical Journal Corp. Ltd, 2026)
Introduction: Threatened miscarriage is a common obstetric complication, and serum progesterone levels are frequently measured to assess pregnancy viability. However, the prognostic accuracy of a single progesterone measurement and the therapeutic efficacy of progesterone supplementation remain areas of clinical debate and heterogeneous evidence. Methods: This comprehensive systematic review synthesized evidence from 57 studies (including meta-analyses, randomized controlled trials, and observational studies) to evaluate the relationship between serum progesterone levels and pregnancy maintenance success in women with threatened miscarriage up to 20 weeks' gestation. Data extraction focused on study population, progesterone measurement methodology, defined pregnancy outcomes, statistical associations, identified thresholds, and confounding factors. Results: The analysis demonstrated a strong inverse relationship between serum progesterone and miscarriage risk. Diagnostic accuracy was high, with a synthesized Area Under the Curve (AUC) of 0.85 (95% CI 0.81–0.88) for predicting viability (Yi Gong et al., 2024). Threshold-dependent performance was evident; levels <6.3 ng/mL showed exceptional specificity (97.3–99.2%) for non-viable pregnancy, while levels ≥20–25 ng/mL strongly predicted viability (B. Ghaedi et al., 2022). The therapeutic benefit of progesterone supplementation was not uniform but significantly modified by patient history and treatment type. Women with recurrent miscarriage, particularly those with three or more losses, derived clear benefit (RR 1.28 for live birth) (A. Coomarasamy et al., 2020). Oral dydrogesterone showed more consistent efficacy (OR 0.43 for reducing miscarriage) compared to vaginal progesterone (Hee-Joong Lee et al., 2017). Discussion: The evidence confirms serum progesterone as a valuable prognostic biomarker. The apparent contradiction in therapeutic trial outcomes is largely explained by population heterogeneity—specifically, previous miscarriage history, route of administration, and baseline progesterone status. Progesterone's mechanism extends beyond hormonal support to include immunomodulation (shifting cytokine balance towards Th2 dominance) and improvement in uteroplacental hemodynamics (Hudic et al., 2011; Czajkowski et al., 2007). Conclusion: A single serum progesterone measurement provides valuable prognostic information in threatened miscarriage, with very low levels being highly predictive of pregnancy failure. Progesterone supplementation is most beneficial for a defined subgroup: women with a history of recurrent miscarriage and early pregnancy bleeding. Clinical implementation should be tailored, moving away from universal supplementation towards a stratified approach based on individual risk factors and biomarker status.